Good Neighbors and Lost Cities: Tourism, the Good Neighbor Policy, and the Transformation of Machu Picchu. - Rice, Mark (Radical History Review, 2017)
An essay is presented which examines how tourism development in Latin America served the aims of U.S. foreign policy during the Good Neighbor era in the context of the Machu Picchu transformation. It examines how economic and cultural actors helped reinvent the site as a national symbol and Hiram Bingham as benevolent Pan-American figure who discovered the site. It also examines how these actors used the language and climate of the policy to pursue their political and cultural goals.